Safety evaluation of percutaneous intrauterine hydrodissection in microwave ablation of uterine fibroids adjacent to the endometrium - Zhao, Zhenlong; Wei, Ying; Wu, Jie; Cao, Shiliang; Yu, Na; Li, Yan; Cai, Wenjia; Yu, Ming’an (Frontiers in Oncology, 2026)
ObjectiveTo assess the safety and efficacy of percutaneous intrauterine hydrodissection as a protective technique during microwave ablation (MWA) of uterine fibroids adjacent to the endometrium.Materials and methodsA retrospective analysis was conducted on patients who underwent MWA with the percutaneous intrauterine hydrodissection strategy. The distribution of isolating fluid, the protective effect of intrauterine hydrodissection, its influence on ablation efficacy, and potential complications were assessed.ResultsA total of 32 female patients were enrolled in the present study. The median age of the patients was 45 years old, with the median target uterine fibroid maximum diameter of 6.9 cm. Thirteen patients presented with fibroid-related symptoms. No evidence of fluid reflux into the pelvic cavity was detected during and after ablation on either CEUS or CT imaging. No case of residual tumor, infection, endometriosis, intestinal injury or bladder injury was observed during follow-up. Symptom improvement was observed in 69.2% (9/13) patients. No patient reported infertility due to intrauterine adhesion or endometrial injury after ablation.ConclusionPercutaneous intrauterine hydrodissection is a safe and effective method for protecting endometrium during MWA of uterine fibroids adjacent to the endometrium.